GAMBARAN KARAKTERISASI DARI EKSTRAK ETANOL LIMBAH RAMBUT JAGUNG MANIS (Zea mays L.) - Yuyun Nikmatus Sholicha; Fita Sari; Dyah Aryantini (As-Syifaa Jurnal Farmasi, 2021)
Traditional plants in Indonesia, have a variety of benefits to overcome various diseases. For example, sweet corn hair waste (Zea mays L), was the residue from corn which is usually used for culinary purposes. Corn silk in previous studies was thought to have pharmacological activity as anti-inflammatory, antidiabetic, and antihypertensive. This study aims to determine the characterization of the ethanol extract of sweet corn hair waste in a hilly area of Kediri, East Java. Characterization to determine the content of active compounds in the ethanol extract of sweet corn hair waste and to ensure the quality of corn hair waste extract when it will be used as raw material for traditional medicine. Characterization includes specific parameters such as screening for metabolites in plant extracts using Thin Layer Chromatography (TLC) and non-specific parameters including determination of water content and specific gravity. The sample used was ethanol extract of sweet corn hair waste (EELRJM) obtained from the hilly area of Kediri, East Java. The results of the specific parameters of the secondary metabolite compound test by TLC indicated that EELRJM contains quercetin compounds of the flavonoid group. Non-specific parameters resulted that the water content of EELRJM did not meet the requirements of the extract monograph because it was suspected that there was an influence on the weather including rainfall.